International trade and productivity growth : exploring the sectoral effects for developing countries - Choudhri, Ehsan U. (2000)
Estimates an empirical relation based on Krugman's 'technological gap' model to explore the influence of the pattern of international trade and production on the overall productivitry growth of a developing country.